The Influence of UI/UX Design and Key Features on User Satisfaction and Loyalty of the Gojek Application among UNJ Students - Muhammad Fathurrahman; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Journal of Digital Business and Global Economy, 2025)
This study analyzes the causal influence of UI/UX Design and Key Features on User Satisfaction and the subsequent effect on User Loyalty within the Gojek application, specifically targeting university students. The research utilized a quantitative associative approach, employing Partial Least Squares-Structural Equation Modeling (PLS-SEM) on a purified model derived from a sample of 100 active students of Universitas Negeri Jakarta (UNJ) via purposive sampling. The findings reveal that both UI/UX Design and Key Features significantly and positively influence User Satisfaction, with Key Features emerging as the dominant predictor. However, despite the achievement of a strong level of User Satisfaction (R2 = 0.609), all causal paths leading to User Loyalty including the mediating path through Satisfaction were statistically rejected. Consequently, the study concludes that application quality has become a hygiene factor, effective in generating user contentment but insufficient as a driver for long-term commitment. This implies that future loyalty strategies must concentrate on external factors such as trust and switching costs.